The effect of budget cuts on C-section rates and birth outcomes: Evidence from Spain - Bertoli, Paola; Grembi, Veronica; Llaneza Hesse, Catalina; Vall Castelló, Judit (Social science & medicine, 2020)
Using data from Spain, we show the impact of significant health-sector budget cuts introduced in 2012 on the rates of cesarean sections and on infant health outcomes at birth, which we use as a proxy for the quality of birth centers. Exploiting a difference-in-differences fixed-effects approach at the hospital level, we estimate a 3% increase in C-sections as a result of the budget restrictions, with no significant consequences on health outcomes at birth. Given the additional evidence in the literature on the negative short- and long-term effects of non-medically indicated C-sections, our paper provides important policy implications for population health.
Keywords: Španělsko; Cesarean Section; Budgets; lidé; porod; Female; Infant; Pregnancy; těhotenství; kojenec; Spain; rozpočty; Parturition; ženské pohlaví; císařský řez; Humans